The impact of project flexibility on project choice and capital structure - Forbes, Shaun (Research of GSB, 2018)
This research highlights the value of Real Options Analysis (ROA) as a process in the evaluation of an oil extraction project in Sub-Saharan Africa. It shows the benefits it can bring to not only the final project evaluation but also to the project design selection process. The research then extends the application of ROA by developing and applying a framework which incorporates the fact that project flexibility has a positive impact on the projects value in the face of downside risk. ROA, by virtue of its explicit cash flow volatility modelling provides a framework for a consideration of the optimal level of project debt. In this case it suggests that the project can carry more debt than would have been acceptable if the more traditional NPV method was used in its evaluation.